Hot corrosion behavior of CoWSi/WSi2 coating exposed to Na2SO4+NaCl salt at 900 °C. Issue 3 (15th February 2016) - Mehrizi, M. Zarezadeh; Eisaabadi, Gh.; Beygi, R.
Abstract: In this study, the high temperature hot corrosion behavior of a CoWSi/WSi2 composite coating was investigated. Hot corrosion studies were performed on CoWSi/WSi2 coated nickel specimens after exposure to a molten Na2 SO4 +NaCl salt environment at 900 °C under cyclic conditions. Thermogravimetric technique was used to establish the kinetics of corrosion. XRD and SEM/EDS techniques were used to analyze the corrosion products. The oxide scale formed on the coating surface was complex and the hot corrosion resistance of coating may be attributed to the formation of oxides and spinels of silicon, cobalt and tungsten. Also, NaCl accelerated the degeneration of the coating because of producing the volatile CoCl2 and thereby oxygen and sulfur could easily penetrate into the coatings and caused the formation of internal oxide and sulfide.